2005
DOI: 10.2527/2005.83122762x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary zinc and iron supplementation on mineral excretion, body composition, and mineral status of nursery pigs1,2

Abstract: Two experiments were conducted to evaluate the effects of dietary Zn and Fe supplementation on mineral excretion, body composition, and mineral status of nursery pigs. In Exp. 1 (n = 24; 6.5 kg; 16 to 20 d of age) and 2 (n = 24; 7.2 kg; 19 to 21 d of age), littermate crossbred barrows were weaned and allotted randomly by BW, within litter, to dietary treatments and housed individually in stainless steel pens. In Exp. 1, Phases 1 (d 0 to 7) and 2 (d 7 to 14) diets (as-fed basis) were: 1) NC (negative control, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
50
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 31 publications
8
50
2
3
Order By: Relevance
“…The composition of feed ingredients provided by NRC (1998) suggested that limestone and monocalcium phosphate contained 3500 and 7500 mg Fe/kg. In agreement with our findings, Rincker et al (2005) had also noticed analyzed Fe values of 189 to 223 mg/kg in the nursery diets that were formulated to contain 50 to 60 mg Fe/kg and they had attributed this high Fe values in the diet to the higher Fe content of feed ingredients including limestone and monocalcium phosphate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The composition of feed ingredients provided by NRC (1998) suggested that limestone and monocalcium phosphate contained 3500 and 7500 mg Fe/kg. In agreement with our findings, Rincker et al (2005) had also noticed analyzed Fe values of 189 to 223 mg/kg in the nursery diets that were formulated to contain 50 to 60 mg Fe/kg and they had attributed this high Fe values in the diet to the higher Fe content of feed ingredients including limestone and monocalcium phosphate.…”
Section: Discussionsupporting
confidence: 91%
“…The Fe concentration of most nursery diets is in excess of the NRC (1998) postweaning dietary Fe requirement of 80 mg/kg. This occurs because many feed ingredients have a high Fe concentration, including monocalcium phosphate and limestone (Rincker et al, 2005). In our previous study we had noticed supplemental Fe (50 to 250 mg/kg) can linearly increase diarrhea incidence and fecal coliform count in weaned pigs (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Zinc oxide mechanism of action as growth promoter appears to go beyond the fulfillment of Zn nutritional needs, and it seems to be more related to improved intestinal health (Zhang and Guo, 2009). In fact, there is growing evidence that ZnO efficacy might be independent from absorption but rather it would act within the gut, as it is well established that above the requirements absorption and retention are no longer increased (Poulsen and Larsen, 1995;Krebs, 2000;Rincker et al, 2005). With this hypothesis in mind, it seems logical to assume that a controlled release of ZnO along the intestine through the use of slow-release techniques might improve its efficacy (Kim et al, 2012;Hu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ZnO-NPs are used in industrial products including cosmetics (sun screens, foot care, ointments and over-the-counter tropical products), pigments and coatings (ultra violet [UV]) protection, fungicide in paints), mouth washes, electronic devices and catalysts [5]. ZnO-NPs have also been used as a dietary supplement in human and live stock because Zn can stimulate the immune system and act in an anti-inflammatory way [6,7]. Many in vitro studies have demonstrated that ZnO-NPs are toxic to mammalian cells and even more toxic than other nanoscale structures of metallic oxide [8][9][10].…”
Section: Introductionmentioning
confidence: 99%